A possible etiology for the dilaceration and flexion of permanent tooth roots relative to bone remodeling gradients in alveolar bone - Richard G Standerwick (Wolters Kluwer Medknow Publications, 2014)
Introduction: Trauma, altered tooth germ position and delayed tooth eruption have been hypothesized as possible causes of tooth root dilacerations and flexion, however these anatomical variations appear more commonly associated with posterior teeth and absence of traumatic history. The Hypothesis: Postulated is that tooth root dilaceration or flexion may be a result of tooth root sheath displacement due to gradients of bone remodeling present within alveolar bone. Evaluation of the Hypothesis: Alveolar bone displays bone remodeling gradients between coronal, apical and basal sections which affect bone plasticity. As a tooth is erupting or experiences delayed eruption, there are other relative dento-skeletal alterations occurring, such as the mesial drift of the dentition and transverse growth of the maxilla. It is plausible that during the physiologic and growth related alteration of the alveolar and basal bones, portions of developing tooth could be found within one or more of the plasticity zones, contributing to alteration of the root sheath and tooth root dilaceration.